Motivating students to learn computer programming in higher education: the SimProgramming approach - Nunes, Ricardo Rodrigues (2021)
This paper presents an action research study aiming to motivate undergraduate students to develop their computer programming learning skills, particularly within the transition from beginner to proficient level. The SimProgramming motivational approach is presented as a didactic proposal for this context. From the results of this iterative research process, we concluded that SimProgramming is a promising tool for teaching computer programming skills in intermediate classes, with potential to be used and/or applied in other educational contexts.